4a+3(a-2)=2(3a-2)

Simple and best practice solution for 4a+3(a-2)=2(3a-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4a+3(a-2)=2(3a-2) equation:


Simplifying
4a + 3(a + -2) = 2(3a + -2)

Reorder the terms:
4a + 3(-2 + a) = 2(3a + -2)
4a + (-2 * 3 + a * 3) = 2(3a + -2)
4a + (-6 + 3a) = 2(3a + -2)

Reorder the terms:
-6 + 4a + 3a = 2(3a + -2)

Combine like terms: 4a + 3a = 7a
-6 + 7a = 2(3a + -2)

Reorder the terms:
-6 + 7a = 2(-2 + 3a)
-6 + 7a = (-2 * 2 + 3a * 2)
-6 + 7a = (-4 + 6a)

Solving
-6 + 7a = -4 + 6a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6a' to each side of the equation.
-6 + 7a + -6a = -4 + 6a + -6a

Combine like terms: 7a + -6a = 1a
-6 + 1a = -4 + 6a + -6a

Combine like terms: 6a + -6a = 0
-6 + 1a = -4 + 0
-6 + 1a = -4

Add '6' to each side of the equation.
-6 + 6 + 1a = -4 + 6

Combine like terms: -6 + 6 = 0
0 + 1a = -4 + 6
1a = -4 + 6

Combine like terms: -4 + 6 = 2
1a = 2

Divide each side by '1'.
a = 2

Simplifying
a = 2

See similar equations:

| 2(4x+3)+4=3x(2x+4) | | 3(x-2)=9(9x+2) | | (-8+5i)(-7+3i)= | | 15-3(2x-9)+x=115 | | -16x^2+6x=56 | | 69.1=3.14*r | | 0.06(y-9)+0.20y=0.16y-0.01(60) | | -6.1x+108.8= | | 6(5n+7)-4(4n+6)=-24 | | 5+4n=7+n | | 4y+2+y=180 | | 19x-9x=20 | | 9x+8=x+40 | | -7.5x+102.3= | | 5+4n=7n | | -6(b-7)-2(b+6)=30 | | 6w+2-3w=26 | | -(3x-5)+2x=7 | | -4f+1= | | 4y+60=9y | | 1000x+50=30 | | -1+m=m-8 | | -27y=-108 | | -6x^2+3=-15 | | 4y+2=180 | | -6f+1=13 | | 3x+60=10x+11 | | 23=-7(6v+7)+5(1-5v) | | 1.9/250=x/650 | | y-18=21 | | 4(2r+12)=6(4r-32) | | -5n+12=7n |

Equations solver categories